The Integration Preference of Sleeping Beauty at Non-TA Site Is Related to the Transposon End Sequences - Zhou, Yiting; Ma, Guangwei; Yang, Jiawen; Gao, Zenghong; Guo, Yabin (Frontiers in Genetics, 2021)
Recently, we proved that Sleeping Beauty (SB) transposon integrates into non-TA sites at a lower frequency. Here we performed a further study on the non-TA integration of SB and showed that 1) SB can integrate into non-TA sites in HEK293T cells as well as in mouse cell lines. 2) Both the hyperactive transposase SB100X and the traditional SB11 catalyze integrations at non-TA sites. 3) The consensus sequence of the non-TA target sites only occurs at the opposite side of the sequenced junction between the transposon end and the genomic sequences, indicating that the integrations at non-TA sites are mainly aberrant integrations. 4) The consensus sequence of the non-TA target sites is corresponding to the transposon end sequence. The consensus sequences changed following the changes of the transposon ends. This result indicated that the interaction between the SB transposon end and genomic DNA may be involved in the target site selection of the SB integrations at non-TA sites.